3D ordered macroporous SmCoO3 perovskite for highly active and selective hydrogen peroxide detection - He, J.; Zhou, W.; Sunarso, J.; Xu, Xiaomin; Zhong, Yijun; Shao, Zongping; Chen, X.; Zhu, H. (Pergamon, 2018)
© 2017 Elsevier Ltd. We reported the direct electrochemical hydrogen peroxide detection on three-dimensionally ordered macroporous SmCoO 3 (3DOM-SmCoO 3 ) perovskite oxide electrode synthesized via a poly (methyl methacrylate) (PMMA) colloidal crystal templating route. The low-cost and simple 3DOM-SmCoO 3 sensor not only overcome the various disadvantages of enzyme- and noble metal-based sensors but also display a superior sensing performance for H 2 O 2 detection. More importantly, using 800 nm PMMA microspheres, a hexagonally ordered macroporous crystalline structure can be created, which features large surface area (20.14 m 2 g -1 ) and large, open, interconnected channels for facile reactants and ions diffusions. The resultant 3DOM-SmCoO 3 synthesized using 800 nm PMMA microspheres template (3D-SC-800) displayed higher sensitivity (715 and 460 µA mM -1 cm -2 ), lower limit of detection (0.004 µM), larger detection linear range (0.1–10,000 µM), and higher selectivity in the presence of interfering species (i.e., glucose, ascorbic acid, dopamine, and uric acid), for H 2 O 2 detection, relative to SmCoO 3 (SC) and SmCoO 3 synthesized using 200 nm PMMA template (3D-SC-200). Our comprehensive electrochemical characterization attributes the superior H 2 O 2 electrooxidation performance of 3D-SC-800 to its fast electron transfer kinetics and diffusion rate. What we demonstrated here bolsters the future opportunity to harness ordered macroporous perovskite oxide-based materials for highly active and selective non-enzymatic H 2 O 2 detection.